Engineers map volcanic lightning. - Patel, P.
Volcanic eruptions are often accompanied by spectacular bursts of lightning-Krakatoa, Mount St. Helens, and Vesuvius have provided some relatively recent examples- and yet these breathtaking bolts are not well understood. Obtaining insight into volcanic lightning, besides being of considerable scientific interest, could make it possible to get earlier warnings of eruptions and might even yield clues to the origins of life. With those ends in mind, electrical engineers at the New Mexico Institute of Mining and Technology, in Socorro, have installed compact sensing stations of their own design at Mount Redoubt in Alaska.